Couples Therapy after the Infidelity of Men: A Controlled Trial Study - صادق باران اولادی; عذرا اعتمادی; سید احمد احمدی; مریم فاتحی‌زاده (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2018)
Aim and Background: Treatment of the couples suffer from infidelity, is a complex and multifaceted process. This study was conducted to evaluate the effectiveness of couple therapy after the infidelity of men. Methods and Materials: This was a quasi-experimental research with pretest, posttest, and follow up, as well as the control group. The study population consisted of all the couples living in Kerman City, Iran, and referred to counseling centers in this city. Those who had the problem of marital infidelity in years 2015-2016 enrolled in this study. The sample included 16 couples that responded desire to divorce scale. Then randomly divided into two groups of control and experimental. In the experimental group, 6-12 therapy sessions were conducted with an average of 9 meetings. Data were analyzed using repeated measures ANOVA. Findings: The treatment decreased couples’ desire to divorce, and the scores in 3 measurements (pretest, posttest, and follow up) were significantly different (P < 0.010). Conclusions: Access to mental health care after infidelity of couples reduces the desire to divorce.